An inverse modeling study of circulation in the Eastern Bering Sea during 2007–2010. Issue 6 (12th June 2016) - Panteleev, Gleb; Yaremchuk, Max; Francis, Oceana; Stabeno, Phyllis J.; Weingartner, T.; Zhang, J.
Abstract: A two‐way nested 4d‐variational data assimilation system is implemented in the Eastern Bering Sea (EBS) to investigate changes in circulation and thermodynamic state for a 3.8 year period. Assimilated observations include data from 19 moorings deployed on the shelf and in the Bering Strait, 1705 hydrographic stations occupied during eight surveys, and remotely sensed sea surface temperature and sea surface height (SSH) data. Validation of the presented 4dVar reanalysis against the output of two sequential data‐assimilative systems (the Bering Ecosystem Study ice‐ocean Modeling and Assimilation System (BESTMAS) and the Arctic Cap Nowcast‐Forecast System (ACNFS)) has shown that the product is more consistent with the observed transports in the Bering Strait and in the EBS interior both in terms of their magnitude and time variability. Analysis of the data‐optimized solution quantifies a sequence of wind‐forced events that resulted in the anomalous heat and freshwater transports through the Bering Strait, including a 28 day long flow reversal that occurred in November 2009 and carried Siberian Coastal Current water down to the Gulf of Anadyr. Lagrangian study of the Arctic‐bound Pacific waters indicates the extreme importance of the cross‐shelf exchange along the path of the Bering Slope Current and quantifies the spectrum of residence times for the waters entering EBS through Unimak Pass and through Aleutian passages. Residence times in the EBS cold pool are diagnosed to be 2–3 times longer than those in the surrounding waters. Key Points: Circulation in the Eastern Bering Sea can be reconstructed through the nested data assimilation Two way nested data assimilation approach converges Transport estimates and particle study are conducted